Intersubunit Concerted Cooperative and cis-Type Mechanisms Modulate Allosteric Gating in Two-Pore-Domain Potassium Channel TREK-2 - Zhuo, Ren-Gong; Peng, Peng; Liu, Xiao-Yan; Yan, Hai-Tao; Xu, Jiang-Ping; Zheng, Jian-Quan; Wei, Xiao-Li; Ma, Xiao-Yun (Frontiers in Cellular Neuroscience, 2016)
In response to diverse stimuli, two-pore-domain potassium channel TREK-2 regulates cellular excitability, and hence plays a key role in mediating neuropathic pain, mood disorders and ischemia through. Although more and more input modalities are found to achieve their modulations via acting on the channel, the potential role of subunit interaction in these modulations remains to be explored. In the current study, the deletion (lack of proximal C-terminus, ΔpCt) or point mutation (G312A) was introduced into TREK-2 subunits to limit K+ conductance and used to report subunit stoichiometry. The constructs were then combined with wild type (WT) subunit to produce concatenated dimers with defined composition, and the gating kinetics of these channels to 2-Aminoethoxydiphenyl borate (2-APB) and extracellular pH (pHo) were characterized. Our results show that combination of WT and ΔpCt/G312A subunits reserves similar gating properties to that of WT dimmers, suggesting that the WT subunit exerts dominant and positive effects on the mutated one, and thus the two subunits controls channel gating via a concerted cooperative manner. Further introduction of ΔpCt into the latter subunit of heterodimeric channel G312A-WT or G312A-G312A attenuated their sensitivity to 2-APB and pHo alkalization, implicating that these signals were transduced by a cis-type mechanism. Together, our findings elucidate the mechanisms for how the two subunits control the pore gating of TREK-2, in which both intersubunit concerted cooperative and cis-type manners modulate the allosteric regulations induced by 2-APB and pHo alkalization.